(untitled) (Historia, 2021)
Between the 1870s and 1913 the idea took root that South Africa, with the exception of areas of dense African settlement, was a white man’s land, although the white community was only 340 000 strong in the late 1870s in a population of 2,2 million, and just over 1,25 million in a population of 6,4 million in 1915. Most of those who propagated white supremacy accepted that a consolidated white group was needed to dominate the black majority. The main obstacle to such a consolidation was the presence of growing numbers of very poor white people on the land and in the towns and cities.Some were destitute and unemployable; others were unskilled or barely skilled.